Rare earth-containing phosphite salts, methods of making, uses and compositions thereof
Patent Information
- Application Number
- CN202411064826.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The flame retardant properties of existing polymer materials are insufficient, and the water resistance and temperature resistance of rare earth oxide products need to be improved.
Rare earth phosphites were prepared by reacting them with inorganic aluminum salts in the presence of water to obtain rare earth phosphites, which were then combined with nylon to form a flame retardant composition. Aluminum diethylphosphonate was added to improve the flame retardant effect.
It significantly improves the flame retardancy, flowability, and impact strength of nylon, and enhances the corrosion resistance of the composition.
Smart Images

Figure CN118978134B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a rare earth phosphite, its preparation method, uses, and composition. Background Technology
[0002] Polymer materials possess advantages such as low density, high strength, good toughness, and good insulation properties, and are widely used in aerospace, electronics, construction, and other fields. However, the flame-retardant properties of some polymer materials need to be improved, requiring the addition of flame retardants during use. The application of rare earth elements in polymer flame-retardant materials has attracted widespread attention.
[0003] CN106315536A discloses a method for preparing rare earth phosphate. The method involves adding a precipitant to a suspension of rare earth carbonate or rare earth oxide at room temperature with continuous stirring until the pH is ≤5. Stirring continues for 5–30 minutes, and the pH is observed to stop rising, indicating the reaction endpoint has been reached. If the pH rises above 2 during stirring, more precipitant is added until the pH is ≤5. Stirring and observation continue until the reaction endpoint is reached. The precipitate is then precipitated, dehydrated, and washed to obtain rare earth phosphate. This method is used for preparing rare earth phosphate.
[0004] CN11483991A discloses a method for preparing lanthanum phosphite. The method involves adding an appropriate amount of water to a reaction vessel, heating and stirring the water while maintaining the temperature at 20–35°C. Lanthanum oxide and a catalyst are then added sequentially to the water, and the mixture is stirred continuously while maintaining the water temperature at 30–35°C. The water, lanthanum oxide, and catalyst react to form a hydrated reactant. This hydrated reactant is added to the reaction vessel containing the hydrated reactant, and phosphoric acid is continuously added dropwise while maintaining the temperature in the hydrated reaction vessel at 40–80°C until the addition is complete. After maintaining the temperature for 2–5 hours, a white rare earth phosphoric acid product is obtained. The rare earth phosphoric acid product is cooled to room temperature and then filtered. The filtered material is placed in an oven at 100–150°C, and the dried material is pulverized to obtain the finished lanthanum phosphite. This method uses rare earth oxides as raw materials, and the resulting product contains hydroxyl groups. The water resistance and temperature resistance of the product need further improvement. Summary of the Invention
[0005] In view of this, one object of the present invention is to provide a method for preparing a rare earth phosphite, wherein the rare earth phosphite prepared by the method of the present invention can effectively improve the flame retardancy of nylon. Furthermore, the nylon composition containing rare earth phosphite prepared by the method of the present invention exhibits good flowability. Even further, the nylon composition containing rare earth phosphite prepared by the method of the present invention exhibits high impact strength and corrosion resistance. Another object of the present invention is to provide a rare earth phosphite. A further object of the present invention is to provide a use of the rare earth phosphite. Yet another object of the present invention is to provide a flame-retardant composition. Still another object of the present invention is to provide a nylon composition.
[0006] The above objectives are achieved through the following technical solutions.
[0007] On the one hand, the present invention provides a method for preparing rare earth phosphites, comprising the following steps:
[0008] Rare earth phosphites and inorganic aluminum salts are reacted in the presence of water to obtain rare earth phosphites.
[0009] According to the preparation method of the present invention, preferably, the rare earth element in the rare earth phosphite is selected from one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, and yttrium;
[0010] The inorganic aluminum salt is selected from one or more of aluminum sulfate, aluminum nitrate, aluminum chloride, and chlorine acetate;
[0011] The molar ratio of aluminum in rare earth phosphites and inorganic aluminum salts is (0.2–3.5):2.
[0012] According to the preparation method of the present invention, preferably, rare earth phosphites are mixed with water, and then inorganic aluminum salts are added;
[0013] The reaction temperature is 50–90℃, and the reaction time is 1–7 h.
[0014] According to the preparation method of the present invention, preferably, it further includes the following step: adding a phosphorous acid solution dropwise to a mixture containing water and rare earth carbonates to obtain rare earth phosphite.
[0015] According to the preparation method of the present invention, preferably, the molar ratio of rare earth carbonate to phosphorous acid is 1:(1.5-4).
[0016] On the other hand, the present invention provides a rare earth-containing phosphite, which is obtained by the above preparation method.
[0017] In another aspect, the present invention provides the use of rare earth phosphites in improving the flame retardant properties and / or flowability of polymers.
[0018] In another aspect, the present invention provides a flame retardant composition comprising the above-mentioned rare earth phosphite and aluminum diethylphosphonate.
[0019] In another aspect, the present invention provides a nylon composition comprising nylon and the above-described flame-retardant composition.
[0020] According to the nylon composition of the present invention, preferably, the nylon composition further includes one or more of antioxidants, lubricants, color masterbatches and glass fibers.
[0021] The rare earth phosphite-containing nylon prepared by the method of this invention can effectively improve the flame retardancy of nylon. Furthermore, the nylon composition containing rare earth phosphite prepared by the method of this invention exhibits good flowability. Even further, the nylon composition containing rare earth phosphite prepared by the method of this invention exhibits high impact strength and corrosion resistance. Attached Figure Description
[0022] Figure 1 The infrared spectrum of lanthanum cerium phosphate obtained in Example 1.
[0023] Figure 2 The infrared spectrum of lanthanum cerium phosphate obtained in Example 2.
[0024] Figure 3 The infrared spectrum of lanthanum cerium phosphate obtained in Example 3.
[0025] Figure 4 The XRD patterns of lanthanum cerium phosphate obtained in Examples 1-3 are shown.
[0026] Figure 5 The images show the XRD patterns of the rare earth-containing phosphites obtained in Examples 1 and 2 and the lanthanum cerium phosphite obtained in Preparation Example 2.
[0027] Figures 6-7 SEM images of different sites of lanthanum cerium phosphite obtained in Example 2.
[0028] Figures 8-11 The images are SEM images of different sites containing rare earth phosphites obtained in Example 1.
[0029] Figures 12-15 SEM images of different sites containing rare earth phosphites obtained in Example 2. Detailed Implementation
[0030] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0031] <Preparation method of rare earth phosphites>
[0032] The method for preparing rare earth phosphites of the present invention includes the following steps: reacting rare earth phosphites and inorganic aluminum salts in the presence of water to obtain rare earth phosphites.
[0033] The rare earth element in the rare earth phosphite is selected from one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, and yttrium. Preferably, the rare earth element in the rare earth phosphite is selected from one or more of lanthanum and cerium. More preferably, the rare earth phosphite is lanthanum-cerium phosphite.
[0034] The inorganic aluminum salt can be a soluble inorganic aluminum salt or a sparingly soluble inorganic aluminum salt. Preferably, the inorganic aluminum salt is selected from one or more of aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum acetate. More preferably, the inorganic aluminum salt is aluminum sulfate.
[0035] The molar ratio of aluminum in the rare earth phosphite and inorganic aluminum salt is (0.2–3.5):2; preferably (0.5–3):2. In some embodiments, the molar ratio of aluminum in the rare earth phosphite and inorganic aluminum salt is (0.8–1.2):2. In other embodiments, the molar ratio of aluminum in the rare earth phosphite and inorganic aluminum salt is (1.8–2.2):2.
[0036] According to one embodiment of the present invention, the rare earth phosphite is lanthanum cerium phosphite. The inorganic aluminum salt is aluminum sulfate. The mass ratio of lanthanum cerium phosphite to aluminum sulfate is (100-500):257; preferably (150-450):257; more preferably (200-400):257. The mass of aluminum sulfate is calculated as aluminum sulfate octadechydrate.
[0037] The reaction temperature can be 50–90°C; preferably 60–80°C; more preferably 70–75°C.
[0038] The reaction time can be 1 to 7 hours; preferably 2 to 6 hours; more preferably 3 to 5 hours.
[0039] The mass ratio of water to rare earth phosphite can be (1-6):1; preferably (2-5):1; more preferably (3-4.5):1.
[0040] According to one embodiment of the present invention, rare earth phosphite and water are mixed and heated to 50-90°C; preferably 60-80°C; more preferably 70-75°C; and then inorganic aluminum salt is added.
[0041] In some embodiments, the process further includes the following steps: cooling the product obtained from the reaction of rare earth phosphite and inorganic aluminum salt, filtering it to obtain a solid product. The solid product is then washed and dried at 90–150°C; preferably, at 100–130°C, to obtain a rare earth phosphite-containing product.
[0042] In some embodiments, the method further includes the step of adding a phosphorous acid solution dropwise to a mixture containing water and rare earth carbonates to obtain rare earth phosphite.
[0043] The rare earth element in the rare earth carbonate is selected from one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, and yttrium. Preferably, the rare earth element in the rare earth carbonate is selected from one or more of lanthanum and cerium. More preferably, the rare earth carbonate is lanthanum cerium carbonate. The lanthanum carbonate content in lanthanum cerium carbonate can be 60–85 wt%; more preferably 65–80 wt%; even more preferably 70–85 wt%. The cerium carbonate content in lanthanum cerium carbonate can be 15–40 wt%; preferably 20–35 wt%; even more preferably 25–30 wt%.
[0044] The molar ratio of rare earth carbonate to phosphorous acid can be 1:(1.5-4); preferably 1:(2-3.5); more preferably 1:(2.4-2.6).
[0045] The temperature of the mixture can be 60–110°C; preferably 70–100°C; more preferably 80–90°C.
[0046] The concentration of the phosphorous acid solution can be 30–70 wt%; preferably 40–60 wt%; more preferably 50–55 wt%. The phosphorous acid solution comprises phosphorous acid and water.
[0047] The mass ratio of water to rare earth carbonate in the mixture can be (2-5):1; preferably (3-4):1.
[0048] After the phosphorous acid solution has been added dropwise, allow the phosphorous acid and rare earth carbonate to react for 1 to 8 hours; preferably 3 to 7 hours; more preferably 5 to 6 hours.
[0049] In some embodiments, the following steps may also be included: filtering the reaction product obtained by reacting phosphorous acid and rare earth carbonate to obtain a filter cake. The filter cake is washed with water at 50–90°C; preferably 60–80°C, and the washed filter cake is dried at 120–170°C; preferably 140–160°C to obtain rare earth phosphite.
[0050] <Rare Earth Phosphites and Their Uses>
[0051] The rare-earth-containing phosphite of the present invention is prepared by the above method. This rare-earth-containing phosphite can improve the flame retardant properties of polymers; and after being added to the polymer, the composition exhibits good flowability. Therefore, the present invention also provides the use of the above-mentioned rare-earth-containing phosphite in improving the flame retardant properties and / or flowability of polymers. In some embodiments, the above-mentioned rare-earth-containing phosphite is used to improve the flame retardant properties of polymers. In other embodiments, the above-mentioned rare-earth-containing phosphite is used to improve the flowability of polymers.
[0052] The polymer is preferably nylon. Nylon may be selected from one or more of PA6, PA66, PA11, and PA12. According to one embodiment of the invention, the nylon is a mixture of PA6 and PA66. The mass ratio of PA6 to PA66 may be 10:(20-60); preferably 10:(30-50); more preferably 10:(35-45).
[0053] <Flame-retardant compositions>
[0054] The flame-retardant composition of the present invention comprises the above-mentioned rare-earth-containing phosphite and aluminum diethylphosphinate. The present invention has found that combining the above-mentioned rare-earth-containing phosphite with aluminum diethylphosphinate results in a better flame-retardant effect.
[0055] The amount of rare earth phosphite can be 1 to 6 parts by weight; preferably 2 to 5 parts by weight; more preferably 3 to 4 parts by weight.
[0056] The amount of aluminum diethylphosphonate can be 8 to 18 parts by weight; preferably 10 to 16 parts by weight; more preferably 12 to 15 parts by weight.
[0057] <Nylon Composition>
[0058] The nylon composition of the present invention comprises nylon and the above-described flame-retardant composition. In some embodiments, it may also include one or more of antioxidants, lubricants, color masterbatches, and glass fibers. The flame-retardant composition is as specifically described above and will not be repeated here.
[0059] The amount of nylon used can be 30-70 parts by weight; preferably 40-60 parts by weight; more preferably 50-55 parts by weight. The nylon can be selected from one or more of PA6, PA66, PA11, and PA12. According to one embodiment of the invention, the nylon is a mixture of PA6 and PA66. The mass ratio of PA6 to PA66 can be 10:(20-60); preferably 10:(30-50); more preferably 10:(35-45).
[0060] The amount of antioxidant used can be 0.1 to 1.5 parts by weight; preferably 0.3 to 1 part by weight; more preferably 0.5 to 0.8 parts by weight. The antioxidant can be a mixture of antioxidant 1098 and antioxidant 608. The mass ratio of antioxidant 1098 to antioxidant 608 can be 2:(1 to 5); preferably 2:(3 to 4).
[0061] The amount of lubricant used can be 0.1 to 1 part by weight; preferably 0.2 to 0.8 parts by weight; more preferably 0.3 to 0.5 parts by weight. The lubricant can be wax powder. According to one embodiment of the present invention, the lubricant is Honeywell AC540A.
[0062] The amount of color masterbatch can be 0.3 to 3 parts by weight; preferably 0.5 to 2 parts by weight; more preferably 1 to 1.5 parts by weight. Black masterbatch is preferred. According to one embodiment of the present invention, the color masterbatch is PA3785 manufactured by Cabot Corporation, USA.
[0063] The amount of glass fiber can be 10 to 50 parts by weight; preferably 20 to 40 parts by weight; more preferably 30 to 35 parts by weight.
[0064] The nylon composition of the present invention can be prepared by the following method: extruding raw materials through a twin-screw extruder to obtain a molded material. Cooling the molded material and then granulating it to obtain the nylon composition.
[0065] The raw materials are described below:
[0066] PA6 grade 2400J was purchased from Hangzhou Juhua Shun New Materials Co., Ltd.
[0067] PA66 grade EPR24 was purchased from Pingdingshan Shenma Engineering Plastics Co., Ltd.
[0068] The glass fiber grade is ECS301UW, purchased from Chongqing International Composite Materials Co., Ltd.
[0069] OP1400 is a compound of aluminum diethylphosphinate and aluminum phosphite, purchased from Clariant Chemicals.
[0070] ADP-33 is aluminum diethylphosphinate, purchased from Qingdao Ouprui New Materials Co., Ltd.
[0071] Lubricant AC540A was purchased from Honeywell.
[0072] Black masterbatch: Grade PA3785, purchased from Cabot Corporation, USA.
[0073] Antioxidant 608 was purchased from Chi-Ti Technology Co., Ltd.
[0074] The testing method is described below:
[0075] If the following test methods require processing into specimens, the nylon composition shall be dried and then processed into specimens at 280°C on an injection molding machine, unless otherwise specified.
[0076] UL94: HB rating is evaluated using a horizontal burning test, while V0-V2 ratings are evaluated using a 500W (125mm) vertical burning test.
[0077] Notched impact strength: Tested according to the method specified in ISO 179-1.
[0078] Preparation Examples 1-3
[0079] Water was added to lanthanum and cerium carbonate (75 wt% lanthanum carbonate and 25 wt% cerium carbonate), the mixture was stirred until homogeneous, and then heated to 90°C to obtain a mixed solution. The mass ratio of lanthanum and cerium carbonate to water in the mixed solution was 1:3. Phosphorous acid and water were then mixed to obtain a 50 wt% phosphorous acid solution.
[0080] A phosphorous acid solution was added dropwise to the mixture. After the addition was complete, the reaction was allowed to proceed for 6 hours to obtain the reaction product. The reaction product was filtered while hot to obtain a filter cake. The filter cake was washed with water at 70°C and then dried at 150°C to obtain lanthanum cerium phosphite.
[0081] The molar ratios of lanthanum and cerium carbonate and phosphorous acid are shown in Table 1. The 1wt% thermogravimetric temperature of lanthanum and cerium phosphorous acid was obtained from the TG curves, and the results are shown in Table 1.
[0082] Figures 1-3 The infrared spectra of lanthanum cerium phosphite obtained in Preparation Examples 1-3 are shown respectively; where 2370-2400 cm⁻¹ -1 The peaks for pH are located to the left and right, ranging from 800 to 1160 cm⁻¹. -1 The absorption peaks at the left and right are for PO and P=O, respectively; 3600 cm⁻¹ -1 The peaks on the left and right are OH peaks.
[0083] Figure 4 The XRD patterns are shown for the lanthanum cerium phosphite obtained in Examples 1-3. Figure 4 It can be seen that the XRD diffraction peaks of lanthanum cerium phosphate obtained in Preparation Examples 1 to 3 are basically consistent.
[0084] Table 1
[0085]
[0086] Example 1
[0087] Add 800g of water to 200g of lanthanum cerium phosphite obtained by the method in Preparation Example 3, stir to disperse and heat to 70°C; then add 257g of aluminum sulfate octahydrate, react at 70°C for 5 hours to obtain the product. After cooling the product, filter to obtain a solid product. Wash the solid product and dry at 120°C to obtain rare earth phosphite.
[0088] The thermal weight loss temperature of 1 wt% rare earth phosphite obtained in this embodiment was 287.6 °C, as determined by TG curve.
[0089] Example 2
[0090] Except for the amount of lanthanum cerium phosphite used, which is 400g, the rest is the same as in Example 1.
[0091] The thermal weight loss temperature of 1 wt% rare earth phosphite obtained in this embodiment was 286.9 °C, as determined by TG curve.
[0092] Figure 5 The images show the XRD patterns of the rare-earth-containing phosphites obtained in Examples 1 and 2, and the lanthanum-cerium phosphite obtained in Preparation Example 2. Figure 5 It can be seen that when aluminum sulfate is added to lanthanum phosphite, the XRD diffraction peak positions of the resulting rare earth phosphite are basically consistent with those of lanthanum phosphite, indicating that the phase of lanthanum phosphite has not changed. However, the addition of aluminum sulfate can make the diffraction peaks of lanthanum phosphite higher and improve the crystallinity.
[0093] Figures 6-7 SEM images of different sites of lanthanum cerium phosphite obtained in Example 2. Figures 8-11 The images are SEM images of different sites containing rare earth phosphites obtained in Example 1. Figures 12-15 These are SEM images of different sites containing rare earth phosphites obtained in Example 2. Figures 6-15 It can be seen that the lanthanum cerium phosphate obtained in Preparation Example 2 is distributed in a rhomboid sheet-like pattern or arranged and agglomerated into an irregular block shape; the rare earth phosphites obtained in Examples 1 and 2 are columnar or oblique rhomboid block grains with an uneven surface and small grain protrusions.
[0094] Examples 3-4 and Comparative Examples 1-4
[0095] 40.2 parts by weight of PA66 (Nylon 66) and 10 parts by weight of PA6 (Nylon 6) were placed in a twin-screw extruder (model: KTS35 / 44D); the materials shown in Table 2 were mixed and then fed into the twin-screw extruder at 260°C through the first side feed port; 30 parts by weight of glass fiber were added into the twin-screw extruder through the second side feed port; the mixture was extruded through the twin-screw extruder to obtain the molded material. The molded material was cooled in a water bath and then granulated to obtain the nylon composition.
[0096] The properties of the nylon composition are shown in Table 2.
[0097] Table 2
[0098]
[0099] Note: Each group of UL94 experiments is conducted five times. A*X means that X of the five experiments have a result of level A.
[0100] Corrosion test
[0101] PA66 and PA6 were placed in a twin-screw extruder (model: KTS35 / 44D); a brass block with a mass of m1 was installed on the die of the twin-screw extruder; a flame retardant (selected from one or more of phosphite, OP1400, ADP-33, and aluminum phosphite), antioxidant 1098, antioxidant 608, AC540A, and black masterbatch were mixed and then added to the twin-screw extruder at 260°C through the first side feed port; glass fiber was added to the twin-screw extruder through the second side feed port; the material was extruded through the twin-screw extruder to obtain the molded material. The molded material was cooled in a water bath and then granulated.
[0102] The total weight of the raw materials (PA66, PA6, flame retardant, antioxidant 1098, antioxidant 608, AC540A, black masterbatch and glass fiber) is 25kg.
[0103] The mass of the brass block on the die head after granulation is measured and recorded as m2. The loss of the brass block is calculated according to the formula (m1-m2) / m1, and the corrosivity of the composition is judged based on the loss of the brass block.
[0104] The selection and proportion of each raw material are shown in Table 3, and the corrosivity is shown in Table 3.
[0105] Table 3
[0106]
[0107] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.
Claims
1. A method for preparing rare earth phosphites, characterized in that, Includes the following steps: Rare earth phosphites are mixed with water, and then inorganic aluminum salts are added and reacted at 50–90°C for 1–7 hours to obtain rare earth phosphites; the molar ratio of aluminum in rare earth phosphites and inorganic aluminum salts is (0.2–3.5):
2.
2. The preparation method according to claim 1, characterized in that, The rare earth elements in the rare earth phosphites are selected from one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, and yttrium; The inorganic aluminum salt is selected from one or more of aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum acetate; The molar ratio of aluminum in rare earth phosphites and inorganic aluminum salts is (0.5–3):
2.
3. The preparation method according to claim 1, characterized in that, It also includes the following steps: A solution of phosphorous acid is added dropwise to a mixture containing water and rare earth carbonates to obtain rare earth phosphite.
4. The preparation method according to claim 3, characterized in that, The molar ratio of rare earth carbonates to phosphorous acid is 1:(1.5-4).
5. A rare earth phosphite, characterized in that, The rare earth-containing phosphite is obtained by the preparation method according to any one of claims 1 to 4.
6. The use of the rare earth phosphite according to claim 5 in improving the flame retardant properties and / or flowability of polymers.
7. A flame-retardant composition, characterized in that, The flame retardant composition comprises the rare earth phosphite and aluminum diethylphosphonate as described in claim 5.
8. A nylon composition, characterized in that, The nylon composition comprises nylon and the flame-retardant composition of claim 7.
9. The nylon composition according to claim 8, characterized in that, The nylon composition also includes one or more of antioxidants, lubricants, color masterbatches, and glass fibers.
Citation Information
Patent Citations
Method for preparing rare-earth phosphorate
CN106315536A
Phosphate material, flame-retardant additive composition, flame retardant composition, halogen-free flame-retardant material, preparation method and application
CN116812894A
Production of rare earth element phosphate having small excess amount of phosphorus than stoichiometric amount
JP1998087309A
